2017
DOI: 10.1002/da.22698
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E gene polymorphism, trauma burden, and posttraumatic stress symptoms in U.S. military veterans: Results from the National Health and Resilience in Veterans Study

Abstract: U.S. military veterans who are APOE ε4 allele carriers and exposed to a high number of traumas may be at increased risk for developing PTSD symptoms than ε4 noncarriers. Greater social support may moderate this association, thereby highlighting the potential importance of social support promoting interventions in mitigating the effect of ε4 × cumulative trauma burden on PTSD risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 80 publications
1
13
0
Order By: Relevance
“…In particular, the presence of the ε4 allele is associated with impaired lipid transport in the periphery and the brain (Marais, 2019). Additionally, ε4 carriers have poorer outcomes after insults to the brain (Mota et al, 2017). In examining the influence of ε4 carrier status on the association between lipids and the diagnosis of TBI and PTSD, the greatest number of peripheral lipid changes were seen in the ε4− mTBI + PTSD group, while this was not the case in the ε4 + mTBI + PTSD group, indicating a differential response to injury in the presence of ε4 allele.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the presence of the ε4 allele is associated with impaired lipid transport in the periphery and the brain (Marais, 2019). Additionally, ε4 carriers have poorer outcomes after insults to the brain (Mota et al, 2017). In examining the influence of ε4 carrier status on the association between lipids and the diagnosis of TBI and PTSD, the greatest number of peripheral lipid changes were seen in the ε4− mTBI + PTSD group, while this was not the case in the ε4 + mTBI + PTSD group, indicating a differential response to injury in the presence of ε4 allele.…”
Section: Discussionmentioning
confidence: 99%
“…Apolipoprotein E (ApoE, encoded by the APOE gene) is a constituent of lipoprotein particles responsible for transporting lipids from the bloodstream to various tissues including the brain (Jonas and Phillips, 2008;Tudorache et al, 2017). Among the three major APOE polymorphisms, the ε4 allele is known to have impaired lipid transport to the brain and is also associated with worse cognitive outcomes in both TBI and PTSD (Mota et al, 2017). ApoE/lipoprotein complexes facilitate lipid transport to the BBB where lipids are processed and subsequently transported into the brain by fatty acid binding proteins (FABP) as well as by other transporters (Mitchell and Hatch, 2011;Sepe et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This systematic review aims to critically appraise the research on risk and protective factors of MCI/dementia among adults with PTSD. Potential and anticipated risk factors may include well-known comorbidities of PTSD, such as major depressive disorder, 23 substance use disorder, 24 obesity 25 and other associated genetic or biological factors (ie, APOE genotype 26 or female sex, 27 respectively). Potential and anticipated protective factors may include cognitive training or physical exercise.…”
Section: Objectivesmentioning
confidence: 99%
“…To date, there have been a limited number of genetic studies of psychological resilience, with most of these investigating candidate genes (e.g., SLC6A4 *5HTTLPR) (Stein, Campbell‐Sills, & Gelernter, ) for what is certainly a highly polygenic trait and, often focusing exclusively on PTSD as the outcome (e.g., APOE epsilon4, or, nitric oxide pathway genes) (Bruenig et al, ; Mota et al, ). One recent study examined self‐reported resilience along with polygenic risk for depression in relation to major depression, finding additive effects, consistent with the notion that psychological characteristics associated with self‐assessed resilience can be considered a buffer against stress (Navrady et al, ).…”
Section: Introductionmentioning
confidence: 99%